Surface Modification using Electric Discharge Machining (EDM) with powder addition - Khan, Ahsan Ali; Mohammed , Baba Ndaliman; Mohd Zain, Zakaria; Jamaludin, Mohammad F.; Patthi, Umar (2011)
Powder mixed electrical discharge machining (PMEDM) is one of the recent innovations for the enhancement of the capabilities of EDM process. In this study,the effects of powder addition on the surface modification of mild steel were investigated. Copper tungsten electrode was used in the machining. Two different powders namely TiC and Al2O3 were used in the study with kerosene as the dielectric medium. The powder types and currents were manipulated to study their effects on the machined surface. The results show that increasing the current leads to increase in recast layer thickness, and the cracks. The Al2O3 powder gave higher layer thickness than TiC powder. TiC Powder addition also produced higher hardness, more tool material and carbon depositions on the work surface than Al2O3 powder.